Answer:
Identity function
Step-by-step explanation:
We are given the following in the question:
Let f(x) be a function.
Then, inverse of f(x) can be written as:
![f^{-1}(x)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29)
The composition function of the function and the reverse function can be found as:
![(f\circf^{-1})(x) = f(f^{-1})(x) = x](https://tex.z-dn.net/?f=%28f%5Ccircf%5E%7B-1%7D%29%28x%29%20%3D%20f%28f%5E%7B-1%7D%29%28x%29%20%3D%20x)
which is an identity function.
Thus, the correct answer is
The identity function, f(x) = x, is formed by the composition of a function and its inverse.